Prolidase-proline oxidase axis is engaged in apoptosis induction by birch buds flavonol santin in endometrial adenocarcinoma cell line - Szoka, Lukasz; Nazaruk, Jolanta; Giegiel, Joanna; Isidorov, Valery (Frontiers in Molecular Biosciences, 2023)
Cancer of the corpus uteri and cervix uteri, collectively ranks second among new cancer cases in women after breast cancer. Therefore, investigation of new anticancer agents and identifying new molecular targets presents a challenge to improve effectiveness of chemotherapy. In this study, antiproliferative activity of flavonoids derived from the buds of silver birch and downy birch was evaluated in endometrial cancer Ishikawa cells and cervical cancer HeLa cells. It was found that flavanol santin reduced viability of both cell lines better than other flavonoids, including apigenin and luteolin. Moreover, this activity was slightly higher than that induced by the chemotherapy drug, cisplatin. Santin promoted intrinsic and extrinsic apoptosis pathways in cancer cells, but it had low toxicity in normal fibroblasts. The mechanisms of impairing cancer cell viability included induction of oxidative proline catabolism, however in different ways in the cell lines used. In HeLa cells, increase of proline oxidation was due to activation of p53 leading to proline oxidase upregulation. In contrast, in Ishikawa cells, having basal proline oxidase level significantly higher than HeLa cells, santin treatment decreased its expression. Nevertheless, proline oxidation was induced in these cells since santin increased expression and activity of prolidase, an enzyme providing proline from protein degradation. In both cell lines, proline oxidation was associated with generation of reactive oxygen species leading to reduction in cell viability. Our findings reveal the involvement of proline oxidase in induction of apoptosis by santin and identify a role of prolidase in proline oxidase-dependent apoptosis.